Relationship between human resource practices with turnover among GCH Retail (M) Sdn Bhd branches at Perak Stores - Fauziah Noor, Mohamed Isa (2020)
Employee turnover provide direct and indirect indicator towards organizational productivity. How to reduce employee’s turnover intention was a very pivotal challenge for today’s HR managers. There are many elements that contribute to turnover intention in organization. The purpose of this study was to examine the relationship between Human Resource (HR) practices and turnover intention. The survey of this research involved 206 respondents among Giant branch store at Perak state and self-administrative questionnaire was used for data collection among respondents. The raw data was analysed by using SPSS version 23 and descriptive and inferential analysis was conducted to fulfill the objectives of the research. Regression analysis revealed that there was significant relationship between HR Practices as in the breakdown of the dimension, training and development, compensation and salary and performance appraisal towards turnover intention among Giant branch store at Perak region. Result of this research able to prepare the alternative solution to support other HR Practices to control that or minimize turnover intention among employees. Future studies are expected to involve a larger number of Giant stores in different states and whole Malaysia.